The anti-hepatitis B virus and anti-hepatotoxic efficacies of solanopubamine, a rare alkaloid from Solanum schimperianum - Mohammad K. Parvez; Mohammed S. Al-Dosari; Md. Tabish Rehman; Adnan J. Al-Rehaily; Ali S. Alqahtani; Mohammad F. Alajmi (Elsevier, 2022)
Chronic liver disease caused by hepatitis B virus (HBV) remains an important health issue. Though there are effective HBV-polymerase inhibitors (e.g., lamivudine), their prolonged use leads to emergence of drug-resistant (polymerase mutant) strains. Several herbal formulations and phytochemicals have been therefore, reported as potential anti-HBV agents with no sign of resistance in experimental and clinical settings. In this study, we assessed the anti-HBV as well as hepatoprotective salutations of solanopubamine, a rare alkaloid isolated from S. schimperianum. In cultured HepG2.2.15 cells, solanopubamine showed marked anti-HBV activity in a time and dose-dependent manner. Solanopubamine (30 μM) efficiently inhibited HBsAg and HBeAg expressions by 66.5%, 70.5%, respectively as compared to 82.5% and 86.5% respective inhibition by lamivudine (2 μM) at day 5. Molecular docking analyses of solanopubamine revealed formations of stable complexes with lamivudine-sensitive as well as lamivudine-resistant polymerase through interactions of catalytic 'YMDD/YIDD' motif residues. Moreover, solanopubamine attenuated DCFH-induced oxidative and apoptotic damage and restored HepG2 cell viability by 28.5%, and downregulated caspase-3/7 activations by 33%. Further docking analyses of solanopubamine showed formation of stable complexes with caspase-3/7. Taken together, our data demonstrates promising anti-HBV and anti-hepatotoxic therapeutic potential of solanopubamine, and warrants further molecular and pharmacological studies.